Fenomenologi Math Anxiety pada Mahasiswa Pendidikan Matematika Sebagai Calon Guru Matematika - Pitaloka, Maharani Dyah; Darmawan, Puguh (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Using a qualitative phenomenological approach, this study examines mathematics anxiety in mathematics education students who are prospective teachers. Based on the questionnaire results, math anxiety is divided into three levels: low, medium, and high. Based on the interview results, students with low anxiety tend to be more confident, students with moderate anxiety tend to be anxious during exams or when teaching material they have not mastered, and students with high anxiety tend to lose focus, especially when learning difficult theoretical concepts. These findings highlight the importance of providing support to students in managing their anxiety so that they can develop into competent and confident math teachers.